(untitled) (TAMADDUN NURI JURNALI, 2025)
Gender linguistics, which is one of the fields of modern linguistics, analyzes the interrelationship between language and gender. Although gender studies in Uzbek linguistics have not yet developed widely, interest in this area has been growing in recent years. This article explores the representation of gender issues in Uzbek linguistics, important research, and the distinctive features of gender lexicon.